The Reproductive Effect of Terbinafine in Ewe: Effects on Estrous Cycle and Ovarian Follicles: Muhannad A. A. AlBayaty* , Eman Rasol AlShaty* and Alaa Karim Jassim ** - AlBayaty, Muhannad A.A. (The Iraqi Journal of Veterinary Medicine, 2012)
Terbinafine is a fungicide given orally with the dose of 100 mg/kg body weight per day for each ewe for 60 days. The vaginal smears of ewe, body and ovarian weight were daily administered at slaughter time; ewes were slaughtered at 60th day. Estrous cycle was affected by showing a significant reduce in the estrous cycle length of each phases of estrous cycle with associated significant increase in the diestrus phase in terbinafine treatment as compared with control group (olive oil treatment as adjuvant) of ewes. There was a significant reduce in the number of follicles and a significant raise in the number of atretic follicles in treated group as compared with control group as well as upsurge the progesterone/estrogen ratio. The body and ovarian weight were significant diminished in terbinafine treatment. These observed effects of terbinafine on the ovarian activity may be due to a direct effect as antiproliferative agent or the hypothalamus - hypophysial - ovarian axis causing hormonal inequality.